Training and development of flipbook learning resources for Master Bimbel in Malang Regency - Fitria Khasanah; Uha Isnaini; Eko Pujiati; Marsono Marsono; Syarifah Inayati (Community Empowerment, 2024)
Master Tutoring aims to help students study at home since the Covid-19 pandemic, when learning at school had to be done online. To realize innovative guidance, there is a system for using learning media, control cards for student progress reports, and regular learning evaluations for tutoring teachers. Apart from that, Master Tutoring plans to package teaching materials that will attract students' interest so that they are more motivated in learning. Thus, the aim of the IndoMS Serving activity is to improve the ability of Master Bimbel tutors in packaging teaching materials in the form of flipbook learning resources. The method used is Master Bimbel tutor training activities, which are carried out in several stages, including: 1) coordination, 2) training on the use of Canva and Heyzine, and 3) flipbook development. The results of this activity show an increase in the knowledge and skills of Master Bimbel tutors in developing teaching materials in the form of flipbook learning resources, which have been applied to Master Bimbel students.